2013
DOI: 10.1007/s11064-013-1106-0
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cells Activation Potentially Contributes to the Upregulation of Stromal Cell-Derived Factor-1α After Optic Nerve Crush in Rats

Abstract: Stromal cell-derived factor-1α (SDF-1α) plays an important role after injury. However, little is known regarding its temporal and spatial expression patterns or how it interacts with glial cells after optic nerve crush injury. We characterized the temporal and spatial expression pattern of SDF-1α in the retina and optic nerve following optic nerve crush and demonstrated that SDF-1α is localized to the glial cells that are distributed in the retina and optic nerve. CXCR4, the receptor for SDF-1α, is expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…CXC chemokine ligand-12 (CXCL12), also called stromal-derived factor 1 (SDF-1), was first defined as a stimulatory factor for B-lymphocyte precursor cells [ 48 ]. It has recently been demonstrated that CXCL12 is a moderate neurite growth-promoting factor for mature RGCs, exerts disinhibitory effects towards myelin and facilitates axon regeneration in the ON [ 8 , 49 ]. Furthermore, the neurite growth-promoting and disinhibitory effects of CXCL12 are blocked by a specific antagonist of its receptor, CXCR4 and by inhibition of the PI3K/AKT/mTOR signalling pathway but not the Janus kinase/Signal transducer and activator of transcription (JAK/STAT3) pathway [ 12 ].…”
Section: Mechanisms Of Rgc Axon Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…CXC chemokine ligand-12 (CXCL12), also called stromal-derived factor 1 (SDF-1), was first defined as a stimulatory factor for B-lymphocyte precursor cells [ 48 ]. It has recently been demonstrated that CXCL12 is a moderate neurite growth-promoting factor for mature RGCs, exerts disinhibitory effects towards myelin and facilitates axon regeneration in the ON [ 8 , 49 ]. Furthermore, the neurite growth-promoting and disinhibitory effects of CXCL12 are blocked by a specific antagonist of its receptor, CXCR4 and by inhibition of the PI3K/AKT/mTOR signalling pathway but not the Janus kinase/Signal transducer and activator of transcription (JAK/STAT3) pathway [ 12 ].…”
Section: Mechanisms Of Rgc Axon Regenerationmentioning
confidence: 99%
“…Activated glial cells in the retina and ON generate multiple pro-regenerative neuro- trophic factors [ 32 , 72 ], such as CNTF and LIF, contributing to axon regeneration. Glial cell activation also potentially contributes to the upregulation of SDF-1α after ONC in rats [ 49 ]. Additionally, a glial scar, primarily consisting of reactive astrocytes and microglia, represents a significant barrier for successful axon regeneration [ 83 ].…”
Section: Mechanisms Of Rgc Axon Regenerationmentioning
confidence: 99%
“…Activated astrocytes typically exhibit increased GFAP expression (Norenberg, ). In a previous study of our rat optic nerve crush model, which uses a Yasargil aneurysm clip, we showed that GFAP expression began in the retina and distal part of the optic nerve crush site 1 day after injury and was maintained for at least 14 days (Feng et al, ; Yang et al, ). Sun et al () reported a 0.5‐fold peak increase in the thickness of processes at 3 and 7 days after optic nerve crush; these processes then returned to a normal size by 2 weeks.…”
Section: Spatial and Temporal Characteristics Of Astrocyte Activationmentioning
confidence: 87%
“…Li et al [27] reported that Cxcl12 (SDF-1a) promoted neural functional recovery by inducing the formation of neuronal connections and suppressing glial scar in a rat spinal cord model. Yang et al [28] reported that the Cxcl12 signalling pathway may function as a bridge between injury and repair in a rat optical nerve injury model. Muse cells have also been reported to be involved in Cxcl12 production [29].…”
Section: Discussionmentioning
confidence: 99%